STUDENTS’ ABILITY IN THE STRUCTURE AND WRITTEN EXPRESSION SECTION IN TOEFL PREDICTION TEST - Tira Nur Fitria (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2021)
This study aims to investigate the students’ ability and their opinions in doing the Structure and Written Expression (SWE) of the TOEFL Prediction test. The result suggests that, on the mean score, 136 non-regular students show a higher average score of 30.68 than 118 regular students’ score of 30.01; on the median score, both regular and non-regular students have the same median score of 36 out of 40 points; while  on the range score, regular students have a minimum score of 4 to 40 correct answers, while non-regular students have a minimum score of 5 to 39 correct answers. Related to their opinions about the test, the students agree that SWE is the most difficult test, thus arguing that studying grammar is essential. Therefore, careful preparation is needed to achieve a maximum score on the test such as having sufficient knowledge of English grammar.